Dysthanasia, euthanasia, orthotanasia: the perceptions of nurses working in intensive care units and care implications Distanasia, eutanasia y ortotanasia: percepciones de los enfermeros de unidades de terapias intensiva e implicaciones en la asistencia Distanásia, eutanásia e ortotanásia: percepções dos enfermeiros de unidades de terapia intensiva e implicações na assistência - Chaiane Amorim Biondo; Maria Júlia Paes da Silva; Lígia Maria Dal Secco (Universidade de São Paulo, 2009)
This study aimed to analyze the perceptions of nurses working in the Intensive Care Unit (ICU) of a University Hospital in Brazil concerning dysthanasia, orthotanasia and euthanasia and characterize potential implications of their perceptions for care. This quantitative study was carried out with the application of a questionnaire to 27 nurses after approval from the institution's Ethics Committee and authorization from participants were obtained. None of the nurses were able to explain euthanasia, half of them explained dysthanasia, and only a third explained orthotanasia, 65.39% recognized some of these processes in their daily practice, 25.9% believed nurses cannot provide any contribution even being familiar with these concepts and their applicability, 82.36% believed that knowledge of bioethical principles is relevant but only 14.81% were able to mention these principles. The bases of nurses' professional practice were not homogeneous and knowledge about the subject was limited. Orthotanasia, bioethical principles and the delivery of humanized care should be the foundation of nursing care. Los objetivos de este estudio fueron analizar las percepciones de los enfermeros que actúan en la UTI de un hospital universitario, en Brasil, sobre distanasia, ortotanasia y eutanasia y caracterizar las posibles implicaciones en la asistencia. Se trata de una investigación con abordaje cuantitativo, aplicándose un cuestionario en 27 enfermeros, después de la autorización del Comité de Ética de la Institución y de la aceptación formal de los sujetos. Ningún enfermero supo explicar la eutanasia, la mitad ofreció un concepto de distanasia y apenas un tercio la ortotanasia. Del total, 65,39% reconocen alguno de esos procesos en su práctica diaria, 25,9% afirman que no creen que el enfermero pueda contribuir sabiendo esos conceptos y su aplicabilidad, 82,36% relataron ser importante saber los principios bioéticos, sin embargo solamente 14,81% supieron citarlos. El fundamento para actuar profesionalmente, entre los enfermeros, no fue homogéneo y el conocimiento acerca del tema todavía es limitado. La búsqueda por la ortotanasia, los principios bioéticos y la humanización de la asistencia deberían ser fundamentos de su asistencia. Os objetivos deste estudo foram analisar as percepções dos enfermeiros que atuam em UTI de um hospital universitário, no Brasil, sobre distanásia, ortotanásia e eutanásia e caracterizar as possíveis implicações na assistência. Trata-se de pesquisa com abordagem quantitativa, aplicando-se questionário em 27 enfermeiros, após autorização do Comitê de Ética da Instituição e aceite formal dos sujeitos. Nenhum enfermeiro soube conceituar eutanásia, metade conceituou distanásia e apenas um terço a ortotanásia. Do total, 65,39% reconhecem algum desses processos em sua prática diária, 25,9% afirmam não acreditar que o enfermeiro pode contribuir sabendo desses conceitos e sua aplicabilidade, 82,36% relataram ser importante saber os princípios bioéticos, mas somente 14,81% souberam citá-los. O fundamento do agir profissional dos enfermeiros não foi homogêneo e o conhecimento acerca do tema ainda é limitado. A busca pela ortotanásia, os princípios bioéticos e a humanização da assistência deveriam ser fundamentos de sua assistência.